REKAYASA PERANGKAT LUNAK KAMUS BAHASA JAWA ONLINE BERBASIS WEB SEBAGAI SARANA PEMBELAJARAN BAHASA JAWA BAGI MASYARAKAT - Marisa, Fitri (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
This study aims to design and implement a system of Java language dictionary online. Programming languages used are PHP, and MySql database system to perform data manipulation process. The results achieved are getting the equivalent word from Indonesian to the Java language with a category All, Krama Inggil (the language of the Alus in the Java language), Krama (the language is in the Java language), or Ngoko (the most abusive language in the Java language ). The results of the product is in the form of a web-based dictionary that can be implemented in the Internet network. Equipped with facilities for web administrator to add vocabulary. Keywords: Dictionaries, Languages Java, PHP, MySql, Internet